2020
DOI: 10.3390/ijerph17217995
|View full text |Cite
|
Sign up to set email alerts
|

Using the Systemic Immune-Inflammation Index (SII) as a Mid-Treatment Marker for Survival among Patients with Stage-III Locally Advanced Non-Small Cell Lung Cancer (NSCLC)

Abstract: The Systemic Immune-Inflammation Index (SII) is an important marker of immune function, defined as the product of neutrophil-to-lymphocyte ratio (NLR) and platelet count (P). Higher baseline SII levels have been associated with improved survival in various types of cancers, including lung cancer. Data were obtained from PROCLAIM, a randomized phase III trial comparing two different chemotherapy regimens pemetrexed + cisplatin (PEM) vs. etoposide + cisplatin (ETO), in combination with radiotherapy (RT) for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…As previously shown in the literature [66][67][68], we retrospectively collected white blood cells (WBC), platelets (PLT), absolute neutrophil (ANC), lymphocyte (ALC), and monocyte (AMC) count obtaining their ratio: NLR, derived NLR (dNLR), lymphocyte-to-monocyte ratio (LMR), platelets-to-lymphocyte ratio (PLR), and systemic inflammation index (SII). dNLR was calculated as ANC/(WBC-ANC) and SII as NLRxPLT.…”
Section: Systemic Inflammation Indexesmentioning
confidence: 99%
“…As previously shown in the literature [66][67][68], we retrospectively collected white blood cells (WBC), platelets (PLT), absolute neutrophil (ANC), lymphocyte (ALC), and monocyte (AMC) count obtaining their ratio: NLR, derived NLR (dNLR), lymphocyte-to-monocyte ratio (LMR), platelets-to-lymphocyte ratio (PLR), and systemic inflammation index (SII). dNLR was calculated as ANC/(WBC-ANC) and SII as NLRxPLT.…”
Section: Systemic Inflammation Indexesmentioning
confidence: 99%
“…It is calculated by P × N / L ratio (SII = P × N / L ratio), where P and N / L are the peripheral platelet count and neutrophil-to-lymphocyte ratio, respectively. At present, studies have shown that there is a certain correlation between the SII and the prognosis of various cancers [ 4 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, several studies have investigated different parameters and nomograms based on inflammation and various hematological variables in order to predict the prognosis of NSCLC patients such as the neutrophil/lymphocyte ratio [44], the thrombocyte/lymphocyte ratio [45], the C-reaction protein-to-albumin ratio [46] and the systemic immune inflammation index [47]. Despite the known effects of age on the inflammation profile [48,49], it is noteworthy to underline the insufficient exploration of this correlation in lung cancer.…”
Section: Discussionmentioning
confidence: 99%